A new computational model based on Archimedean copula for probabilistic unbalanced linguistic term set and its application to multiple attribute group decision making. (February 2020) - Han, Bing; Tao, Zhifu; Chen, Huayou; Zhou, Ligang; Liu, Jinpei
Highlights: Construct a new computational model of PULTS based on Archimedean copula. Develop some novel closed operational laws for PULTS. Provide some new probabilistic unbalanced linguistic aggregation operators. Abstract: This paper proposes the concept of the probabilistic unbalanced linguistic term set which considers not only the probability of linguistic variables but also the non-uniform and non-symmetric distribution of linguistic labels. A new computational model on basis of Archimedean copula and corresponding co-copula is developed to deal with probabilistic unbalanced linguistic information. The most advantage of the model is that it can keep the closure of the operation. Some operational properties and particular cases are further investigated. We present the concepts of Archimedean copula weighted probabilistic unbalanced linguistic arithmetic average aggregation operator and Archimedean copula weighted probabilistic unbalanced linguistic geometric average aggregation operator, some properties are also discussed. Finally, the effectiveness and universality of the developed approach are illustrated by a hospital selection and comparison analysis. A sensitivity analysis is also performed to test the robustness of proposed methods.